Dacnusa (Dacnusa) pseudolugens TOBIAS 1998 - Papp, J. (Zenodo, 2007)
Dacnusa (Dacnusa) pseudolugens TOBIAS, 1998, ♂ new (Figs 8–11) – 1 ♂: No. 282. – Described from Far East of Asiatic Russia (Magadan Region, Yakutiya, Primorski Krai). New to the fauna of Korea. – The Korean male specimen deviates in a few features from the female: (1) head in dorsal view twice as broad as long, head between temples a bit broader than between eyes (Fig. 8); (2) penultimate flagellomere 1.6 times as long as broad; (3) hind femur 4.1 times as long as broad distally (Fig. 9); (4) pterostigma twice as long as 1– R1 (Fig. 10); (5) pair of keels of first tergite distinct (Fig. 11); (6) legs brown to dark brown. Published as part of Papp, J., 2007, Braconidae (Hymenoptera) From Korea Xxii. Subfamily Alysiinae, pp. 1-38 in Acta Zoologica Academiae Scientiarum Hungaricae 53 (1) on page 10, DOI: 10.5281/zenodo.5731826